2016
DOI: 10.1051/bioconf/20160701023
|View full text |Cite
|
Sign up to set email alerts
|

The cost of grape mechanical harvesting is more economical than the manual harvest?

Abstract: Abstract. The objective of this study was to compare the costs of mechanical harvesting and grape manual in commercial property of "Santana do Livramento", "Rio Grande do Sul" (RS) -Brazil. The study was conducted commercial vineyard, over four years (2013)(2014)(2015)(2016), throughout this period we evaluated 154.9 ha on the mechanical harvesting of grapes and; 366.7 ha on the grapes of manual harvesting; for both types of collection were recorded all costs thereof, including annual fixed fees (depreciation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, the economic level of the mechanized harvesting deployment is also vital. However, even here, studies by other authors (Jobbágy et al, 2018(Jobbágy et al, , 2021Dominguez and del Aguila, 2016;Pezzi and Martelli, 2015;Tudisca et al, 2013) are in favour of mechanization of harvesting and consider the mechanized harvesting of grapes a way to increase the profitability of wine production.…”
Section: Losses In Manual Harvestingmentioning
confidence: 77%
“…However, the economic level of the mechanized harvesting deployment is also vital. However, even here, studies by other authors (Jobbágy et al, 2018(Jobbágy et al, , 2021Dominguez and del Aguila, 2016;Pezzi and Martelli, 2015;Tudisca et al, 2013) are in favour of mechanization of harvesting and consider the mechanized harvesting of grapes a way to increase the profitability of wine production.…”
Section: Losses In Manual Harvestingmentioning
confidence: 77%
“…Although the main objective of mechanizing the grape harvest is to reduce the need for labor, wine growers demand information about the costs of this investment to weigh their choices. Therefore, here we will show a study developed by Domingues & Aguila (2016) comparing mechanized and manual harvesting costs. The authors evaluated 154.9 hectares under mechanical harvesting and 366.7 hectares with manual harvesting and reported that the cost of manual harvesting was 133.3% higher than the value obtained for mechanical harvesting.…”
Section: Use Of Self-propelled Harvestersmentioning
confidence: 99%
“…It should be pointed out, however, that the revenue shown in Table 1 is for the first year. Over the span of 25 years (under which the PV is under warranty), the efficiency of solar PV farm will decrease each year of all PV technologies is about 1%/year [67] and the majority of modules should be less than this at around 0.5%/year [68]. However, the functional lifetime of the PV can be much greater than that and with proper care, grapevines can live for 50 to 100 years or more.…”
mentioning
confidence: 99%